PORTRAYING THE USE OF AUTHENTIC MATERIALS IN EFL READING CLASSES: A STUDY ON STUDENTS’ PERCEPTIONS - Mayarega, Hevin; Rahmawati, Henny; Azami, Mochamad Imron (Premise: Journal of English Education and Applied Linguistics, 2023)
Using authentic materials in EFL reading classes is essential as a medium to help students practice their reading skills. This study uses mixed methods to determine student perceptions, motivation, and anxiety when using authentic texts in EFL reading classes. The participants of this study were 19 students of a university in Malang in the third semester. The data collection instruments used include questionnaires and interviews. The results of this study indicate that students tend to give positive perceptions. Nevertheless, it is undeniable that some students give negative responses for several reasons. Positive responses indicate that students feel authentic texts have many benefits. In contrast, negative responses indicate that they cannot understand the contents of the reading and do not feel the benefits that can be obtained. The level of student motivation is also higher than student anxiety. Students feel motivated because they can improve their English skills, gain knowledge, and feel challenged. However, they also encounter difficulties that make them anxious when reading authentic texts. The reason is that they find many uncommon words, language, and sentence structures. For future researchers, doing more research on students and conducting more profound interviews is suggested so that the data obtained is more varied than the current one.